La caligrafía y su incidencia durante el proceso de producción de textos literarios en los estudiantes de cuarto año de Educación General Básica en el área de Lengua y Literatura de la Escuela “Isabel la Católica” parroquia Guanujo, cantón Guaranda, provincia Bolívar, periodo lectivo 2024-2025. - Peña Ocampo, Jadira Lisbeth. (2025)
This research addressed the issue of handwriting and its incidence during the process of production of literary texts, because many students face significant difficulties in writing, which prevents them from writing or drafting literary texts, using their imagination and creativity. The main objective of the research was to determine the incidence of calligraphy in the process of production of literary texts in students of fourth year of General Basic Education in the area of Language and Literature of the “Isabel la Católica” School, Guanujo parish, Guaranda canton, Bolivar province, period 2024- 2025. Subsequently, the development of the theoretical framework was based on the review of academic papers and articles based on the independent and dependent variable. In addition, a research methodology with a mixed approach, which includes qualitative and quantitative, was proposed. According to the analysis carried out, it is concluded that the data obtained were useful for the design of a guide of didactic activities to strengthen the development of calligraphy through the production of literary texts in students of General Basic Education, followed by several activities that will be applied during their school day, in order to improve the problem of calligraphy in the production of literary texts.